PENGUATAN LITERASI KONSUMEN MUSLIMAH TERHADAP KOSMETIK HALAL DAN THAYYIB BERBASIS KOMUNITAS MAJELIS TAKLIM DI MASJID JAMI' BINTARO JAYA - Umi Khusnul Khotimah (DEVELOPMENT: Journal of Community Engagement, 2022)
The modern lifestyle of urban Muslim women in the Bintaro area, South Tangerang, has undergone a fundamental paradigm shift in the last decade. Cosmetics and skincare are no longer viewed merely as aesthetic commodities but have transformed into constitutive elements of social identity. However, this phenomenon presents an epistemological paradox: amidst high consumption rates, there is a significant literacy gap regarding critical halal points and the technical implications of products on the validity of worship (thaharah). This research, designed as a research-based community service report, aims to empower the congregation of Masjid Jami' Bintaro Jaya to transform from passive consumers into smart consumers with theological and scientific awareness. Using the Participatory Action Research (PAR) method with a cycle of Planning, Action, Observation, and Reflection, this study intervenes in the community's mindset through a participatory andragogy approach. Field findings in the pre-intervention phase revealed that 70% of participants prioritized brand image and public figure testimonials over halal certification legality. Through strategic actions such as the "Cosmetic Bag Dissection" workshop and simple scientific experiments on water permeability in cosmetic products, a radical cognitive shift occurred. Participants were not only able to identify critical ingredients like porcine collagen and human placenta but also built a collective defense mechanism through the "Cosmetic Hijrah" movement. The study concludes that the PAR approach is effective in bridging the gap between state regulations (Halal Product Assurance Law) and daily consumption practices, as well as repositioning the mosque as a center for progressive halal lifestyle education amidst the national regulatory transition period of 2019-2020.